A new measurement approach for identifying high-polluting jobs across European countries - Causa, Orsetta (OECD Economics Department Working Papers, 2024)
This paper develops a novel classification of high-polluting occupations for a large sample of European countries. Unlike previous efforts in the literature, the classification exploits country-level data on air polluting emission intensity by industry. The country-level data allows to capture important cross-country differences, due to differences in technology and in production focus. Applying the new classification to European Labour Force Survey data shows that, on average across the countries covered, about 4% of workers are employed in high-polluting jobs, ranging from 9% in Czechia and the Slovak Republic to around 2% in Austria. These shares do not exhibit any clear decreasing trend over the past decade. High-polluting jobs are unequally distributed, being over-represented among men, workers with lower and medium educational attainment and those living in rural areas